Sustainable fashion for all: brand awareness / Abdul Muhaimin Abdul Rahim - Abdul Rahim, Abdul Muhaimin (Faculty of Art and Design, 2020)
Sustainability in fashion is new in the Malaysia scene. Countless brands and products are thriving out with sustainability to protect mother nature at all cost.